A brief review of equatorial ionization anomaly and ionospheric irregularities. Issue 4 (16th August 2018) - Balan, Nanan; Liu, LiBo; Le, HuiJun
Abstract : Following a brief history and progress of ionospheric research, this paper presents a brief review of the recent developments in the understanding of two major phenomena in low and mid latitude ionosphere—the equatorial ionization anomaly (EIA) and involved equatorial plasma fountain (EPF) and ionospheric irregularities. Unlike the easy‐to‐understand misinterpretations, the EPF involves field perpendicular E × B plasma drift and field‐aligned plasma diffusion acting together and plasma flowing in the direction of the resultant at all points along the field lines at all altitudes. The EIA is formed mainly from the removal of plasma from around the equator by the upward E × B drift creating the trough and consequently the crests with small accumulation of plasma at the crests when the crests are within ~±20° magnetic latitudes and no accumulation when they are beyond ~±25° magnetic latitudes. The strong EIA under magnetically active conditions arises from the simultaneous impulsive action of eastward prompt penetration electric field and equatorward neutral wind. Intense ionospheric irregularities develop in the post‐sunset bottom‐side equatorial ionosphere when it rises to high altitudes, and evolve nonlinearly into the topside. Pre‐reversal enhancement (PRE) of the vertical upward E × B drift and its fluctuations amplified during PRE provide the driving force and seed, with neutral wind and gravity waves being the primary sources. At low solar activity especially in summer when fast varying PRE is absent, the slow varying gravity waves including large scale waves (LSW) seem to act as both driver and seed for weak irregularities. At mid latitudes, the irregularities are weak and associated with medium scale traveling ionospheric disturbances (MSTIDs). A low latitude minimum in the occurrence of the irregularities at March equinox predicted by theoretical models is identified. The minimum occurs on the poleward side of the EIA crest and shifts equatorward from ~25° magnetic latitudes at high solar activity to below 17° at low solar activity.